Lornoxicam Side Effects May Lead to Surgical Mismanagement, in Case of Postoperative Intra-Abdominal Collection: A Case Report and Literature Review - Mohammad Bukhetan Alharbi (Case Reports in Surgery)
Postoperative collection is a known complication of abdominal surgery, especially after major surgery; however, minor surgical procedures may also be associated with this phenomenon. Utilization of nonsteroidal anti-inflammatory drugs, such as lornoxicam, and the adverse effects thereof, may affect the surgeon’s judgment regarding the need for, and extent of, draining of these collections. Here I report the case of a 25-year-old male who presented with perforated acute retrocaecal subhepatic appendicitis complicated by pleural effusion and a small abdominal collection. The pleural effusion resolved almost completely over time. However, the patient showed incomplete recovery, as demonstrated by nausea, vomiting, and mood disturbance along with abdominal pain, tachycardia, and a persistent small abdominal collection. We initially suspected infection caused by a highly virulent type of bacteria and planned to perform percutaneous drainage. However, owing to skin erythematic changes, administration of lornoxicam was ceased, which resulted in complete recovery of the symptoms and consequently in avoidance of unnecessary invasive intervention to drain the abdominal collection. These findings suggest that the utilization and adverse effects of some painkillers for postoperative pain, such as lornoxicam, may affect the surgeon’s judgment regarding the most appropriate surgical workup in cases of postoperative fluid collection.